Grape seed proanthocyanidin extract inhibits ferroptosis by activating Nrf2/HO-1 and protects against diabetic kidney disease - Tingting Li; Hao Wang; Baolei Chang; Heng Lu; Ruirui Yang; Haowei Zhang; Haiyan Li; Yusong Ding (PLoS ONE, 2025)
Background The main pathological characteristic of diabetic kidney disease (DKD) is renal dysfunction caused by tubular injury. Ferroptosis is a recently discovered form of cell death closely linked to renal tubular injury in DKD. Nuclear factor erythroid-2 related factor 2/heme oxygenase 1(Nrf2/HO-1) is crucial in controlling ferroptosis. Grape seed proanthocyanidin extract (GSPE) mitigates renal dysfunction in DKD by activating Nrf2/HO-1 pathway. However, the role of GSPE in protecting against DKD through ferroptosis modulation has been insufficiently explored. Methods Streptozotocin (STZ)-induced diabetic rat models and HK2 cells cultured with high glucose were used as experimental objects in this study. HE and PAS staining was used to observe the morphological changes of rat kidney. Fe 2+ and reactive oxygen species (ROS) levels as well as apoptosis were determined by fluorescent staining. Transferrin receptor protein 1(TfR1), acylcoa synthetase long chain family member 4(ACSL4), glutathione peroxidase 4 (GPX4), Nrf2 and HO-1 proteins were detected by western blot. Subsequently, Nrf2 was knocked down and oxidative stress and ferroptosis were observed in HK2 cells. Results In vivo and vitro result showed that GSPE treatment significantly lessened renal impairment, oxidative stress, and ferroptosis in DKD, while the application of Ferrostatin-1 (Fer-1) notably amplified the anti-ferroptotic effect of GSPE. Moreover, the anti-ferroptotic effect of GSPE was markedly diminished after Nrf2 expression was downregulated in HK2 cells. Conclusion GSPE treatment reduced ferroptosis in DKD by modulating the Nrf2/HO-1. In conclusion, our results underscore the significance of ferroptosis in DKD and present new perspectives on the protective effects of GSPE in this condition.